24.3k views
8 votes
Solve the literal equation for y.
2x – xy = 3

User Cforbish
by
4.9k points

2 Answers

9 votes

Answer:


y = - (3)/( x) + 2

Explanation:

So we want y to be on a side by itself.

2x-xy=3

Subtract 2x from each side

-xy=3-2x

divide each side by -x


y = (3)/( - x) + 2

Hope this helps! If you have any questions on how I got my answer feel free to ask. Stay safe!

User Tushar Nikam
by
5.1k points
9 votes

Answer:

Explanation:

2x-xy=3

-xy=3-2x

y=3-2x/x

User Salman Raza
by
5.3k points